(Invited) Evaluation of Coupled Triple Quantum Dots with Compact Device Structure. (1st August 2017) - Takahashi, Yasuo; Uchida, Takafumi; Tsurumaki-Fukuchi, Atsushi; Arita, Masashi; Fujiwara, Akira
Abstract : A simple method to evaluate the triple quantum dots (TQDs) coupled in series with relatively large inter-dot coupling capacitances is proposed. The device concepts are useful for the applications for quantum computing and single-electron transfer devices in which the coupling capacitances play an important role. The electrical characteristics of series TQDs are evaluated by the use of Monte Carlo simulations. Here, the TQD structure is the same that actually fabricated with the simple method of pattern-dependent oxidation (PADOX) and additional oxidation of the silicon nanowire on a SOI wafer with three control gates. To evaluate the nine gate capacitances among the three control gates and three QDs, we use the stability diagram of the TQDs by employing the simultaneous gate-voltage scanning method in which the three gate voltages are scanned with different sweeping ratio. The method enables us to clarify the position of hidden current peaks and thus boundaries of charge transition of the three QDs in the stability diagram, which makes it possible to evaluate all of the nine gate capacitances of the TQD.